Don't Miss Me: Midfoot Sprains, A Point-of-Care Review - Koetser, Inge C.J.; Espinosa Hernández, Enrique A.; Kerkhoffs, Prof. dr. Gino M.M.J.; Goedegebuure, Simon; Smithuis, Frank F.; Maas, Prof. dr. Mario (Seminars in Musculoskeletal Radiology, 2023)
Athletes practicing high-contact sports are exposed to an increased risk of midfoot injuries, namely midtarsal sprains. The complexity of reaching an accurate diagnosis is clearly depicted in the reported incidence of midtarsal sprains, ranging from 5% to 33% of ankle inversion injuries. Because the focus of the treating physician and physical therapist is on lateral stabilizing structures, midtarsal sprains are missed at initial evaluation in up to 41% of patients, with delayed treatment as a result.Detecting acute midtarsal sprains requires a high degree of clinical awareness. Radiologists must become familiar with the characteristic imaging findings of normal and pathologic midfoot anatomy to avoid adverse outcomes such as pain and instability. In this article we describe Chopart joint anatomy, mechanisms of midtarsal sprains, clinical importance, and key imaging findings with a focus on magnetic resonance imaging. A team effort is essential to provide optimal care for the injured athlete.
Keywords: midfoot sprain; midtarsal injury; Chopart; athlete; ankle ligaments